Immunological memory 2 - Gray, David (Henry Stewart Talks, 2020)
Quantity and quality memory maintenance, Memory cell survival and homeostasis, Concept of resource ‘niches’ for survival, A role for antigen in memory longevity, Memory and protective immunity